PARKINSONISMO SIFILITICO - CASO, AGUSTIN (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1949)
Erythroblasts from the bone marrow of the rabbit were studied in the stained smear for general morph, indices of maturation and karyo-kinesis, dimensions of the nucleus and cytoplasm, and the nucleo-plasmic relations Tables and graphs of these measureme
BOL MEN BAN REF JAL
Keywords: PARKINSONISMO SIFILITICO; CIENCIAS DE LA VIDA; BIOLOGIA CELULAR; CULTIVO CELULAR